2017
DOI: 10.1007/s12039-016-1220-z
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetics Investigation on the Nitro-Nitrite Rearrangement Mediated Thermal Decomposition of High Temperature Monoclinic Phase of 1,1-Diamino-2,2-Dinitroethylene (γ-Fox-7)

Abstract: 1,1-Diamino-2,2-dinitroethylene (DADNE), commonly known as FOX-7, is one of the novel high energy density molecules recently developed along with CL-20, TNAZ and ADN. DADNE is well-known for its insensitive nature and this has motivated the research in understanding the thermal and explosive decomposition behaviour of DADNE. We have studied the thermal decomposition kinetics of DADNE employing two isoconversional methods viz., Friedman's differential method and Vyazovkin's non-linear integral method. For the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…As shown in Figure 6 , three different samples had a similar exothermic decomposition process, which indicated that solid-phase decomposition kinetics dominated their thermal decomposition process. The DSC curves showed the first endothermic peak for the β → γ phase transition [ 21 ] and the second endothermic peak for the γ → δ transition [ 22 ]. After the phase transitions, there were two successive exothermic decomposition processes of FOX-7: the first with the peak at ca.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 6 , three different samples had a similar exothermic decomposition process, which indicated that solid-phase decomposition kinetics dominated their thermal decomposition process. The DSC curves showed the first endothermic peak for the β → γ phase transition [ 21 ] and the second endothermic peak for the γ → δ transition [ 22 ]. After the phase transitions, there were two successive exothermic decomposition processes of FOX-7: the first with the peak at ca.…”
Section: Resultsmentioning
confidence: 99%
“…DSC curve of spherical FOX-7 exhibits two endothermic peaks and one exothermic peak, identical to the TG results. The rst endothermic peak (117.29 C) for the a / b phase transition and the second endothermic peak (157.61 C) for the b / g transition, 9,26 which conrmed that the DSC crystal form transition peak of FOX-7 is related to the particle size of the sample. 27 It should be noted that, compared with raw FOX-7, the two steps of spherical FOX-7 almost merging into a single peak (238.53 C).…”
Section: Thermal Decomposition Characteristicsmentioning
confidence: 99%
“…The decomposition of DADNE at different heating rates was experimentally studied by the TGA and DSC methods [13]; four steps of decomposition with E a from 160 to 148 kJ mol −1 (DSC) and about 200 kJ mol −1 (TGA) were observed [13]. In the authors' opinion, the major rate‐determining step is the formation of NO after the nitro‐nitrite rearrangement or the formation of HONO after hydrogen transfer to oxygen.…”
Section: Introductionmentioning
confidence: 99%